2014
DOI: 10.1038/ncomms4707
|View full text |Cite
|
Sign up to set email alerts
|

Marine ice regulates the future stability of a large Antarctic ice shelf

Abstract: The collapses of the Larsen A and B ice shelves on the Antarctic Peninsula in 1995 and 2002 confirm the impact of southward-propagating climate warming in this region. Recent mass and dynamic changes of Larsen B’s southern neighbour Larsen C, the fourth largest ice shelf in Antarctica, may herald a similar instability. Here, using a validated ice-shelf model run in diagnostic mode, constrained by satellite and in situ geophysical data, we identify the nature of this potential instability. We demonstrate that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
118
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(130 citation statements)
references
References 35 publications
11
118
1
Order By: Relevance
“…Previous iceshelf collapses are thought to have been accomplished by surface meltwater-driven crevassing (van der Veen, 1998;van den Broeke, 2005;Banwell et al, 2013) and ice-front retreat past a "compressive arch" in strain rates (Doake et al, 1998;Kulessa et al, 2014). We conceive several interconnected mechanisms by which LCIS stability could be compromised: (1) ice-front retreats past a compressive arch; (2) increased surface melting causes firn depletion and meltwater-driven crevassing; (3) decreased ocean freezing or increased melting depletes marine ice, permitting the propagation of crevasses; (4) collapse of the remnant LBIS opens a new ice front at the northern margin of LCIS; (5) ungrounding from Bawden Ice Rise removes an ice-front pinning point; (6) ice thinning and acceleration enhances the propagation of crevasses and weakens shear zones.…”
Section: Ice-shelf Stabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…Previous iceshelf collapses are thought to have been accomplished by surface meltwater-driven crevassing (van der Veen, 1998;van den Broeke, 2005;Banwell et al, 2013) and ice-front retreat past a "compressive arch" in strain rates (Doake et al, 1998;Kulessa et al, 2014). We conceive several interconnected mechanisms by which LCIS stability could be compromised: (1) ice-front retreats past a compressive arch; (2) increased surface melting causes firn depletion and meltwater-driven crevassing; (3) decreased ocean freezing or increased melting depletes marine ice, permitting the propagation of crevasses; (4) collapse of the remnant LBIS opens a new ice front at the northern margin of LCIS; (5) ungrounding from Bawden Ice Rise removes an ice-front pinning point; (6) ice thinning and acceleration enhances the propagation of crevasses and weakens shear zones.…”
Section: Ice-shelf Stabilitymentioning
confidence: 99%
“…Kulessa et al (2014) showed that LCIS has a large region in which the second principal stress is tensile and thus offshore of a compressive arch. Kulessa et al (2014) also considered the angle between the flow and first principal stress under the assumption that rifts strike perpendicular to flow, arguing that a first principal stress aligned with the flow would tend to open rifts, rendering the ice shelf unstable. LCIS has a large region with first principal stress across flow, stabilising the ice shelf according to this measure.…”
Section: Ice-shelf Stabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…However, previous modeling studies for the LBIS and wider Antarctic Peninsula did not incorporate these key processes, as they were either flow line approaches, studies that did not include a migrating grounding line or neglected the collapse of the ice shelves all together, or studies where the grounding line migration was directly prescribed [Vieli et al, 2006[Vieli et al, , 2007Barrand et al, 2013Barrand et al, , 2006Kulessa et al, 2014]. Results of these studies are expected to be incomplete, in particular, for glaciers that were previously buttressed by an ice shelf or glaciers that are flowing into ice shelves that are vulnerable to collapse.…”
Section: Introductionmentioning
confidence: 99%